Intravenous thrombolysis with 0.65 mg/kg r-tPA may be optimal for Chinese mild-to-moderate stroke - Cui, Yu; Yao, Zhi-Guo; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background: Intravenous recombinant tissue plasminogen activator (r-tPA) with 0.9 mg/kg is the standard treatment for acute ischemic stroke, but it remains unclear whether it is optimal for all patients. We aimed to determine optimal dose of r-tPA for Chinese stroke based on the data from INTRECIS study. Methods: From INTRECIS cohort, patients receiving intravenous r-tPA within 4.5 hours onset were included. According to r-tPA dose, patients were assigned into 7 groups (from 0.60 mg/kg to 0.90 mg/kg). The primary outcomes were the proportion of excellent functional outcome and symptomatic intracranial hemorrhage. Results: Overall, 2666 patients were included: 156 in 0.60 mg/kg group, 117 in 0.65 mg/kg group, 127 in 0.70 mg/kg group, 188 in 0.75 mg/kg group, 154 in 0.80 mg/kg group, 359 in 0.85 mg/kg group, and 1565 in 0.90 mg/kg group. After adjustment for baseline characteristics, only 0.65 mg/kg group had significantly higher proportion of excellent functional outcome than 0.90 mg/kg group (79.5% vs 71.4%, odds ratio = 1.833, 95% confidence interval = 1.006 to 3.341, adjusted p = 0.048). The subgroup analysis showed no evidence of differences in the odds of having a primary outcome between two groups by age, admission NIHSS, onset to thrombolysis time, and TOAST classification. There was no significant difference in symptomatic intracranial hemorrhage between groups. Conclusions: Our study presented the first evidence that intravenous thrombolysis with 0.65 mg/kg r-tPA may be optimal for Chinese mild to moderate stroke. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT 02854592.